Avaliação do tipo de carregamento, pela análise de elementos finitos, sobre a resistência de união ao cisalhamento da interface metal/porcelana (Ni-Cr/vita omega 900) - Kojima, Alberto Noriyuki [UNESP] (2005)
The purpose of this study was to compare the devices influence piston, stainless steel strip and chisel, used in shear bond tests to verify the resistance in the metal/porcelain interface. The values depend on a complex tensions combination and resultants produced during the application of the forces in the specimens and the variations in the methodologies of the tests result in differents resistances values to shear bond strength, what complicates the standardization and the direct comparison between different researchers. They were used 36 specimens (Ni-Cr, Wiron 99 – Bego and porcelain Vita Omega 900 - Vita ) divided into three groups (n = 12). The specimens were submitted to the shear bond strength in a universal testing machine EMIC (model DL-2000, São José dos Pinhais – PR), with a crosshead speed of 0,5 mm/min. After, the representative sets of each group were examined in scanning electronic microscopy for the observation of the failures. The finite elements analysis was used to verifiy the tensions distribution on the specimens. The results were submitted to the analysis of variance and to Tukey's Test in the level of 5%, it was verified that there was significant statistically difference between the three devices used. The present study showed that the piston device obtained better results than the conventional method ISO 11405 and strip